(untitled) (Scientific journal of the Fergana State University, 2024)
In the article, the theoretical-methodological foundations of researching the socio-ethical views of the thinkers of the Timurid era, the hermeneutic bases of their socio-ethical views, the educational significance of the socio-ethical views of the thinkers of the Timurid era in New Uzbekistan are studied. The formation of thinkers of the Timurid period and their socio-ethical views was also analyzed.